THE MEANINGFULNESS OF DEMOCRATIC VALUES IN THE ARGUMENTS OF THE FIRST INDONESIAN PRESIDENTIAL CANDIDATE DEBATE IN 2024 - Agahirber, Agahirber; Sunarso, Sunarso (JURNAL SOCIOPOLITICO, 2024)
The realization of democratic values is a serious effort to alleviate some of the problems that occur in Indonesia. This matter was discussed in depth by three candidates for President of Indonesia in 2024; Anies Rasyid Baswedan, Prabowo Subianto, and Ganjar Pranowo at the inaugural debate event which took place on December 12 2023. In this regard, this research seeks to analyze the meaningfulness of democratic values contained in the debate arguments for the 2024 Presidential Candidates of the Republic of Indonesia as well as the driving factors. This research uses a content analysis method with a qualitative approach, focusing on democratic values in the first debate session of the 2024 Indonesian Presidential candidates. Data was collected through transcription of debate videos and other sources such as books and journal articles; national and international. Analysis was carried out using a thematic approach so that the validity of the data was obtained through diligent observation. The research results show that Anies Rasyid Baswedan's argument tends to include the value of equality before the law with six (6) findings, Prabowo Subianto's argument focuses more on respect for human rights with four (4) findings, and the same goes for Ganjar Pranowo who focuses its arguments towards respecting human rights with five (5) findings.Crucial issues such as unequal access to justice, human rights violations and corruption are the driving factors for the 2024 Indonesian Presidential candidates to raise debate arguments that contain democratic values.